Influence of Epoxy Resin on the Compressive Strength of Laminated Bamboo Short Columns - Javil Egi Pratama Abdurahman; Fadly Ardiyatna; Muhammad Nur; Moh Haifan (Pusat riset dan Inovasi Nasional, 2026)
The use of laminated bamboo columns as alternative building materials has attracted increasing attention, particularly as a substitute for wood in construction. Bamboo lamination techniques enable the production of structural materials with tailored mechanical properties. Numerous previous studies have investigated the compressive strength of laminated bamboo short columns subjected to various treatments. This study aims to evaluate the compressive strength and failure patterns of laminated bamboo short columns under compression loading. The experimental program included physical and mechanical characterization of bamboo, followed by compression testing of laminated bamboo short columns with dimensions of 10 cm × 10 cm × 30 cm. Three treatment variations were examined: untreated laminated columns, epoxy resin–coated columns, and steel plate–reinforced columns. The results indicate that untreated laminated bamboo columns exhibited an average compressive strength of 28.044 MPa, with cracking concentrated at the top of the column. Epoxy resin–coated laminated bamboo columns achieved an average compressive strength of 28.774 MPa, showing crack formation distributed across several regions of the column. Steel plate–reinforced columns demonstrated the highest average compressive strength of 31.138 MPa, with failure localized in the region between the steel plates. These findings provide valuable insights into the effectiveness of different treatment methods in enhancing the compressive performance and failure characteristics of laminated bamboo columns.